2017
DOI: 10.1080/10942912.2017.1303707
|View full text |Cite
|
Sign up to set email alerts
|

Stability of lime essential oil emulsion prepared using biopolymers and ultrasound treatment

Abstract: The objective of this study was to investigate the kinetic stability of lime essential oil emulsion using gum arabic (GA) and whey protein isolate (WPI) biopolymers as emulsifiers and stabilizers. Different solid compositions were evaluated: GA, GA/WPI (1:1) and WPI, as well as oil concentration (5.0, 7.5 and 10% w/w). Emulsions were prepared using an ultrasonic homogenizer. Viscosity, oil droplet size, zeta potential, pH and conductivity were measured to predict the emulsion stability over a period of 4 h (es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 67 publications
3
31
0
Order By: Relevance
“…In some studies about the application of US in grape (Aadil et al, ) and apple juice (Abid et al, ), the authors also did not observe any significant variation of the pH with increased US application time. Also, in lime oil emulsions with GA (Campelo et al, ), no significant variation of the pH values with variation of the GA concentration was observed.…”
Section: Resultsmentioning
confidence: 92%
“…In some studies about the application of US in grape (Aadil et al, ) and apple juice (Abid et al, ), the authors also did not observe any significant variation of the pH with increased US application time. Also, in lime oil emulsions with GA (Campelo et al, ), no significant variation of the pH values with variation of the GA concentration was observed.…”
Section: Resultsmentioning
confidence: 92%
“…The PDI value was correlated to the spread of the particle size distribution and its values goes from 0 to 1. When the PDI value was close to 0, the physical stability of the emulsion was ensured, and was represented by a narrow size distribution [37][38][39]. Generally, values below 0.3 result in uniformity among the particle size distribution and good physical stability [26,40].…”
Section: Emulsion Characterizationmentioning
confidence: 99%
“…Moreover, some studies revealed that the use of MD with a high dextrose equivalent (DE), as in this case (DE20), might contribute to increasing the sample hygroscopicity due to a great number of ramifications with hydrophilic groups. Thus, considering an average environmental relative humidity of 33%, samples may easily absorb moisture from the ambient air during powder handling after spray drying [38,[54][55][56]. Therefore, the handling and storage of the powder are crucial processes that must be carefully carried out to avoid the humidity uptake.…”
Section: Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to determine the effect of ultrasonic homogenization on the physical properties of the emulsion with various types of vegetable oil such as olive oil (Kaltsa, Gatsi, Yanniotis, & Mandala, 2014), lime essential oil (Campelo et al, 2017), orange peel essential oil (Hashtjin & Abbasi, 2015), palm oil (Consoli et al, 2017), rapeseed oil (O'sullivan, Murray, Flynn, & Norton, 2015), sunflower oil (Leong et al, 2009) including coconut milk (Du Le, 2015;Iswarin & Permadi, 2012;Jena & Das, 2006). An extensive study on the effect of SC concentration and other types of emulsifiers on the stability of coconut milk was conducted by Tangsuphoom and Coupland (2008).…”
Section: Introductionmentioning
confidence: 99%